Blood on the doorstep : the politics of preventive action - Rubin, Barnett R. (Century Foundation Press, 2002)
"In this book, the founding director of the Council on Foreign Relations' Center for Preventive Action analyzes the nature and causes of contemporary armed conflict. Using case studies developed from extensive fieldwork in the Balkans, Central Asia, and Africa, Barnett Rubin illustrates how global trade in arms, drugs, and other products can cause conflict or make it far more violent." "The terrorist attacks of 2001 made it painfully clear that the blood of violent regional conflict can reach the American doorstep. However, ethnic conflicts, failing states, and humanitarian disasters in the world's poorest regions can be averted or ameliorated with effective early attention, according to Rubin. He calls for flexible partnerships among states, international organizations, and nongovernmental organizations to reduce the structural causes of violent conflict and to prevent their escalation."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved